2020
DOI: 10.21203/rs.3.rs-22177/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effectiveness of an online intervention in stimulating injury-preventive behaviour in adult novice runners. Results of a randomised controlled trial.

Abstract: Background In addition to the beneficial health effects of being active, running is also associated with a risk of sustaining injuries. The online intervention Runfitcheck was developed to stimulate injury-preventive behaviour among adult novice runners. The objective of this study was to evaluate the effectiveness of Runfitcheck on injury-preventive behaviour among adult novice runners. Design Randomised controlled trial Methods A randomised controlled trial with a follow-up period of five months was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a previous study by Kemler et al , positive effects were found of the Runfitcheck on injury preventive behaviour of novice runners. 14 The assumption was made that increased injury preventive behaviour using the Runfitcheck would ultimately lead to a decrease in RRIs. However, this study did not demonstrate these positive effects to prevent RRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study by Kemler et al , positive effects were found of the Runfitcheck on injury preventive behaviour of novice runners. 14 The assumption was made that increased injury preventive behaviour using the Runfitcheck would ultimately lead to a decrease in RRIs. However, this study did not demonstrate these positive effects to prevent RRI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interventions for preventing RRI in novice runners are important 8 9. Although such interventions are limited, the studies available have shown their positive effect on behavioural aspects in runners 13 14. Studies evaluating the effect of such online interventions on RRIs are limited as well 15 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation